Probabilitas Induksi Komponen Bioaktif Tanaman Kratom pada Kajian Antidiabetes dan Antiobesitas - Ajeng Maula Ningrum; Martha Christina; Taslia Rizky Putri; Cico Jhon Karunia Simamora (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Kratom (Mitragyna speciosa Korth.) is widely used by the surrounding community as a traditional antidiabetic and antiobesity drug due to its high content of secondary metabolite compounds. The purpose of writing this review is to find out the bioinduction influence of Bacillus thuringiensis and Pseudomonas fluorescens and to find out the presence of an increase in secondary metabolites. Method: Writing and assessing source problems related to using literature study methods. Results: Kratom leaf methanol extract contains secondary metabolites of alkaloid groups, flavonoids, steroids/terpenoids, phenols and saponins. The main compound content of kratom leaves classified as alkaloids is mitragynine that has not been found in other plants. The administration of non-pathogenic bacteria such as Bacillus thuringiensis and Pseudomonas fluorescens can induce plant defenses and can accumulate the production of phenol compounds and flavonoids in plants. Conclusion: Based on the literature search results, kratom can indeed function as an antidiabetic and antiobesity and induction of microbes, namely Bacillus thuringiensis and Pseudomonas fluorescens bacteria can increase the content of secondary metabolites of plants. Through the increase in secondary metabolites, the efficacy of plants is higher to overcome health problems, namely antidiabetics and antiobesity.